Reduced convergence within the Tibetan Plateau by 26 Ma?. Issue 13 (3rd July 2017) - Meng, Jun; Coe, Robert S.; Wang, Chengshan; Gilder, Stuart A.; Zhao, Xixi; Liu, Hao; Li, Yalin; Ma, Pengfei; Shi, Kai; Li, Shuai
Abstract: Understanding the dynamics of double‐thickening and uplifting of the Tibetan crust requires constraints on the magnitude and timing of crustal shortening. New elongation/inclination ( E / I )‐corrected paleomagnetic data from ~26–22 Ma sediments indicate that the latitude of southern Tibet in the early Miocene was 31.1/−6.8/+5.2°N, not significantly different from today. This implies that the southern margin of Asia, which was at 21–24°N latitude from the Late Cretaceous to the early Eocene, advanced 8–10° northward between the early Eocene and the latest Oligocene. Our results therefore suggest that at least 900–1100 km of continental shortening and significant regional uplift of the plateau occurred between the early Eocene and late Oligocene. Our results suggest that N‐S intra‐Asian convergence was considerably reduced around 26 Ma, corresponding to a transition from compression to extension within the Tibetan Plateau. Plain Language Summary: Two critical questions involving the geodynamic evolution of the Tibetan plateau are (i) when did a compression‐dominated tectonic regime change to an extension‐dominated tectonic regime on the plateau and (ii) how does this timing correlate with double thickening of the crust? Here we provide paleomagnetic evidence for the timing, magnitude, and partitioning of intra‐Asian convergence. Our results imply a first‐order constraint of 900–1100 km north‐south shortening concentrated within the interval from 53 to 26 Ma. This suggests that a fundamental change at ~26 Ma occurred in the geodynamics of the Tibetan Plateau marked by a reduction in large‐scale convergence and compressive deformation. The implication is that significant regional uplift of the proto‐Tibetan Plateau occurred within the ~55–26 Ma interval. The paleolatitude, paleoclimate, and topography of south central Tibet seen at present were likely established around 26 Ma. Key Points: Southern Tibet was around the similar latitude in the early Miocene as it is today N‐S convergence at 900–1100 km was concentrated within the interval 55–26 Ma N‐S intra‐Asia convergence was reduced at ~26 Ma